2008
DOI: 10.1111/j.1365-2036.2008.03864.x
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel polyps and tumours: endoscopic detection and treatment by double‐balloon enteroscopy

Abstract: SUMMARYBackground Double-balloon enteroscopy has allowed us not only to inspect deeply the small bowel but also to carry out interventions for diseases of the small bowel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 28 publications
2
53
0
4
Order By: Relevance
“…In the past, the diagnosis of small bowel tumors was made mainly through SBFT, abdominal CT, or even laparotomy; however, more accurate diagnosis for small bowel tumors became possible after the development of CE and DBE. The frequency of small bowel tumors in patients who receive CE has been reported to be 1.6-8.9% [4][5][6][7][8][9][10], while the frequency in patients who receive DBE is 10.0, 11.5 and 13.9% according to studies performed in Germany, Portugal, and Japan, respectively [15][16][17]. This difference is because DBE is usually performed to confirm abnormal findings that have been detected by other imaging studies, including CE.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, the diagnosis of small bowel tumors was made mainly through SBFT, abdominal CT, or even laparotomy; however, more accurate diagnosis for small bowel tumors became possible after the development of CE and DBE. The frequency of small bowel tumors in patients who receive CE has been reported to be 1.6-8.9% [4][5][6][7][8][9][10], while the frequency in patients who receive DBE is 10.0, 11.5 and 13.9% according to studies performed in Germany, Portugal, and Japan, respectively [15][16][17]. This difference is because DBE is usually performed to confirm abnormal findings that have been detected by other imaging studies, including CE.…”
Section: Discussionmentioning
confidence: 99%
“…Until only recently, primary surgical resection and IOE were the only available possibilities for treating polyps in the mid-small bowel in patients with PJS [73][74][75][76] . DBE and video capsule enteroscopy have changed this approach and it is now possible to not only to perform endoscopic surveillance and diagnose these lesions, but also to resect them [37,58,73,77,78] . Many reports on DBE have suggested that this new method may be able to replace at least IOE in many circumstances [63,79,80] .…”
Section: Overall Experience Of Pjs Patientsmentioning
confidence: 99%
“…A recent retrospective multicenter survey in four countries has indicated a complication rate of 0.8% (13/1728) in diagnostic procedures and 4.3% (27/634) for therapeutic DBE, and there were no fatal cases [63,84,85] . During DBE, careful attention must be paid not to insufflate too much air, because this induces intestinal loop formation and impedes deep advancement [73] . With CO2 insufflation, we solved this problem completely.…”
Section: Overall Experience Of Pjs Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu has ta la rın kap sül en dos ko pi ya da çift ba lon ente ros ko pi ile de ğer len di ril me le ri öne ril mek tedir. 12,13 Bu tet kik ola nak la rı ol ma yan mer kez ler de, bi zim has ta la rı mız da da ol du ğu gi bi MR-en te rok lisis yol gös te ri ci ol mak ta dır.…”
Section: Discussionunclassified